PO190 Anti-musk positive myasthenia gravis at a tertiary centre. (1st December 2017) - Ahrabian, Dariush; Chinthapalli, Krishna; Foley, Imelda; Kullmann, Dimitri; Howard, Robin
Abstract : Muscle-specific tyrosine kinase (MuSk) myasthenia gravis (MG) is a distinct and characteristic condition. We reviewed 27 MuSK-MG patients treated at the National Hospital for Neurology and Neurosurgery. Twenty-three patients were female with median age of onset of 30.5 years and median follow-up of 8.5 years. At presentation, sixteen patients had generalised weakness and eleven pure ocular involvement. In the latter group, nine became generalised and two remained ocular. At maximum severity, the pattern of involvement was: ocular (n=24) bulbar (n=22); limb (n=18); respiratory (n=18) and seven required intensive care admission. Twenty-five required long-term oral immunosuppression (prednisolone (n=24); azathioprine (n=18); mycophenolate (n=8); rituximab (n=2)). Fourteen patients received intravenous immunoglobulin, six received plasma exchange and seven underwent thymectomy. Two patients died during follow-up: One from respiratory failure and one of unrelated causes. Twelve patients were in remission, of whom eight required continuing immunosuppression. Ten had mild symptoms and three had poorly controlled MG. Five patients required long-term non-invasive ventilation, all of whom had bulbar and respiratory involvement at presentation. Most patients with MuSK-MG develop generalised weakness and there is a significant risk of respiratory involvement and myasthenic crisis. Sustained remission off medications is unusual and the majority will need long-term immunosuppression.